Enhancing Mathematical Learning Achievements for First-Grade Students at SDN Kebagusan 04 Pagi, South Jakarta Through Cooperative Learning Model Implementation - Okta Rosfiani; Cecep Maman Hermawan; Irma Saraswati; Rahmah, Aqila Azizah; Kevin Dilly Junior; Achmad Abdur Rozaq (Enigma in Education, 2024)
Mathematics is an abstract discipline that involves concepts and ideas derived from logical reasoning and practical applications in the real world. The objective of this study is to assess the academic achievements in mathematics, specifically in the area of basic flat shapes, among first-grade students at SDN Kebagusan 04 Pagi, located in South Jakarta. The study will utilize the cooperative learning method known as group investigation. The study will utilize the cooperative learning method known as group investigation, which is a specific type of cooperative learning model. This study employs a cyclical framework based on the Kemmis & McTaggart model, which comprises four stages: planning, implementation, observation, and reflection. The research findings indicated a rise in students' proficiency in mathematics. The mean scores of the students are as follows: pre-cycle 63.00, cycle I 66.00, and cycle II 82.00. Additionally, there was a rise in the proportion of students who attained the minimum level of completeness. Specifically, in the pre-cycle, 33.33% of students achieved this level, while in cycle I, the percentage increased to 40.00%, and in cycle II, it further rose to 80.00%. In conclusion, the implementation of the group investigation cooperative learning approach has the potential to enhance students' academic achievements and comprehension of mathematical concepts.